Vexin is upregulated in cerebral cortical neurons by brain‐derived neurotrophic factor - Hisatsugu Koshimizu; Shingo Suzuki; Anna Kawai; Ryuichiro Miura; Ken‐ichi Ohta; Takanori Miki; Naoki Adachi; Hidetada Matsuoka (Wiley, 2020)
Abstract Aim Chromosome 8 open reading frame 46 (C8orf46), a human protein‐coding gene, has recently been named Vexin. A recent study indicated that Vexin is involved in embryonic neurogenesis. Additionally, some transcriptomic studies detected changes in the mRNA levels of patients with psychiatric and neurological diseases. In our previous study, we sought for target genes of brain‐derived neurotrophic factor (BDNF) in cultured rat cortical neurons, finding that BDNF potentially leads to the upregulation of Vexin mRNA. However, its underlying mechanisms are unknown. In the present study, we assessed the regulatory mechanisms of the BDNF‐induced gene expression of Vexin in vitro. Methods We reanalyzed ChIP‐seq data in various human organs provided by the ENCODE project, evaluating acetylation levels of the 27th lysine residue of the histone H3 (H3K27ac) at the Vexin locus. The transcriptomic effects of BDNF on rat Vexin (RGD1561849) were evaluated by real‐time quantitative PCR (RT‐qPCR) in primary cultures of cerebral cortical neurons, in the presence or absence of inhibitors for signaling molecules activated by BDNF. Results The Vexin locus and its promoter region in the brain angular gyrus show higher acetylation levels of the H3K27 than those in other organs. Stimulation of cultured rat cortical neurons, but not astrocyte, with BDNF, led to marked elevations in the mRNA levels of Vexin, which was inhibited in the presence of K252a and U0126. Conclusion The upregulated H3K27ac in the brain may be associated with the enriched gene expression of Vexin in the brain. It is indicated that BDNF induces the gene expression of Vexin in the cortical neurons via the TrkB‐MEK signaling pathway.